The Effect of Therapeutic Communication of Nurses on the Mental Health Condition of Patients in the Inpatient Room - Seftiani Utami; Qamariah; Rahmania Siregar (CV. Get Press Indonesia, 2026)
The mental health of patients in inpatient settings is a critical concern in healthcare services, and nurses’ therapeutic communication plays an important role in influencing patients’ psychological conditions. Limited understanding of this relationship may negatively affect recovery. This study aimed to examine the effect of nurses’ therapeutic communication on patients’ mental health in the inpatient unit. This study used a quantitative design with a correlational approach. The research was conducted at RSUD M. Natsir Solok, involving 50 inpatients selected through purposive sampling based on inclusion criteria. Data were collected using two instruments: a therapeutic communication questionnaire to evaluate nurse–patient interactions and the Self Reporting Questionnaire (SRQ) to assess patients’ psychological and emotional conditions. Data analysis was performed using the chi-square test. Ethical principles were applied by obtaining informed consent and ensuring data confidentiality. The results showed that 70% of patients perceived good therapeutic communication from nurses. Regarding anxiety levels, 50% of patients experienced moderate anxiety and 30% reported high anxiety. The chi-square test indicated a significant relationship between therapeutic communication and anxiety levels (p = 0.035). In conclusion, therapeutic communication positively influences patients’ mental health, emphasizing the need for structured training to enhance nurses’ communication skills.